Frozen coconut (Cocos nucifera Linn.) water concentrate as solvent for urinary stone - Macalalag, Myra Michelle L.
This study deals on the preservation of coconut/buko water to be used as kidney stone solvent. Low preservation technique, specifically freezing, was employed to transform young coconut water or buko water into buko nectar (the frozen coconut water concentrate). Comparative on the dissolving capacity of buko nectar and buko water was accomplished using the chemotriptic procedure. The comparative test involving 6 subjects describes the ingestion of Buko Water and Buko Nectar and urine collection, thereafter. The collected urine specimen were used to dissolve kidney stone (s) in the Modified Flowby Dissolution Apparatus. From the results, Buko Nectar can be further explored as a treatment for nephrolithiasis for its range of dissolution was 17.62 - 18.37 ppm Ca.